Spatial symmetry and contrasting controls of surface pH and aragonite saturation state in the western North Pacific - Li, Cheng-long; Wu, Yingxu; Chen, Kui; Lin, Hongmei; Chen, Liqi; Qi, Di (Frontiers in Marine Science, 2023)
Oceanic uptake of anthropogenic CO2 causes decreases in seawater pH and aragonite saturation state (Ωarag), a process known as ocean acidification (OA). The western North Pacific is a hotspot for anthropogenic CO2 sink, whereas the spatiotemporal variabilitiesy of OA metricspH and Ωarag and their controlling mechanisms remain unexplored. In this study, we provide high-frequency and high-precision underway measurements of sea surface pCO2 and pH to investigate the distribution and drivers of OA metrics across the different hydrochemical gradients in the western North Pacific in late spring 2018, a season with the highest primary production of year. Our results show that the surface pH reached near air-sea equilibrium in the subtropical zone, but gradually increased northward across the Kuroshio Recirculation (KR) zone, and peaked in the Kuroshio Extension (KE) zone. We found that sea surface temperature exhibited the most prominent role on regulating pH, which was also counteracted by the effects of air-sea gas exchange and vertical mixing. In contrast, the distribution of Ωarag largely mirrored pH and was governed by air-sea gas exchange and vertical mixing,. The the effects of these two factorswhich on Ωarag were enhanced by temperature. Biological activity thrived in the KE zone to increase both pH and Ωarag, which further reinforced the latitudinal pattern of pH but weakened that of Ωarag. These findings are based on the direct in situ measurements of pH, and improve our understanding of the spatiotemporal variability of OA metrics in the western North Pacific.